The Rationale Divinorum Officiorum of William Durand of Mende: A New Translation of the Prologue and Book One. Translated by Timothy m. thibodeau - Stevenson, Kenneth (The journal of theological studies, 2008)
‘Durandus studies’ have come on in leaps and bounds in recent years. In 1990, Pierre-Marie Gy, OP, convoked a conference at Mende where medievalists with different specialisms looked at the life and work of Durand from varying perspectives; and he edited a collection of these papers which was published two years later (see JTS, ns 44 [1993], p. 496). Among the contributors were Anselme Davril, OSB, monk of St-Benoît-sur-Loire, who had been studying the Rationale divinorum officiorum for many years, and Timothy Thibodeau, an American scholar, whose 1988 Notre Dame doctoral thesis was on book 5 of the Rationale.